Comparison of sampling adequacy between OPD based pipelle biopsy and in- patient conventional D&C, presented with abnormal uterine bleeding - Hina Tabassum , Azra Saeed Awan , Sabeen Ashraf , Omair Ashraf ,Asia Raza , Asma Iqbal, Hina Tabassum , Azra Saeed Awan , Sabeen Ashraf , Omair Ashraf ,Asia Raza , Asma Iqbal (Journal of Rawalpindi Medical College, 2019)
Objective: To determine agreement on adequacy of sample by pipelle biopsy and conventional dilatation and curettage in patients with abnormal uterine bleeding. Study design: Cross sectional study Setting and Duration of Study: Department of Obstetrics and Gyneacology, Islamic International Medical College Trust, Railway Hospital Rawalpindi. Study was carried out over a period of six months (11-07-2012 to 14-01-2013). Patients and Methods: 84 patients presented with abnormal uterine bleeding age 45 years and older, attended Gynecology department of Railway Hospital Rawalpindi. Who qualified the inclusion criteria were enrolled in this study by non-probability consecutive sampling technique. The diagnostic intervention for endometrial sampling was by pipelle device and by conventional D&C. Both procedures were performed in the OT at the same time.First the pipelle sample was taken and was labeled as “A” then conventional D&C was performed and was labeled as “B”. Both samples were sent to the pathologist, who was blinded as to the method of sample collection for histopathology assessment. Adequacy of the sample was assessed as per operational definition. A data base was made in SPSS version 17. Kappa statistics was applied to assess the agreement. Results: Out of 84 patients, 80 (98.8%) of the patients had adequate sample with Pipelle Biopsy as compared to conventional curettage and dilatation (D & C). We therefore recommend the use of pipelle biopsy as a first line tool for endometrial assessment for our setups instead of D&C. Conclusion: Our study concluded that the Pipelle biopsy is a useful and convenient method to the patients and physicians as ompared to D&C performed in the operating theatre. It is useful in obese and high-risk patients with minimum chances of perforation of uterus due to its soft flexible tip.